Internet Governance 2.0.1.4: The internet balkanization fragmentation - Sérgio Alves (International Telecommunications Society (ITS), 2014)
The text addresses some of the definitions and origins of the term "Internet Balkanization." Drawing upon U.S. constitutional law and interstate commerce regulations, it argues that the term also carries strong connotations on the realms of jurisdiction and commerce. The text adds examples of how this effect affects the businesses of creative companies that are exploring innovative markets in the United States, and suggests that the term "Internet Balkanization" should not be used in the context of international negotiations of Internet Governance, due to its pejorative connotations and misleading implications.
Keywords: 330; internet balkanization; internet governance; balkanizion; privacy; fragmentation; cybersecurity; international telecommunication union; sharing economy; netmundial; data localization